Identification of Novel Viruses in Amblyomma americanum, Dermacentor variabilis, and Ixodes scapularis Ticks - Rafal Tokarz; Stephen Sameroff; Teresa Tagliafierro; Komal Jain; Simon H. Williams; D. Moses Cucura; Ilia Rochlin; Javier Monzon; Giovanna Carpi; Danielle Tufts; Maria Diuk-Wasser; Jory Brinkerhoff; et al. (mSphere, 2018)
ABSTRACT Ticks carry a wide range of known human and animal pathogens and are postulated to carry others with the potential to cause disease. Here we report a discovery effort wherein unbiased high-throughput sequencing was used to characterize the virome of 2,021 ticks, including Ixodes scapularis (n = 1,138), Amblyomma americanum (n = 720), and Dermacentor variabilis (n = 163), collected in New York, Connecticut, and Virginia in 2015 and 2016. We identified 33 viruses, including 24 putative novel viral species. The most frequently detected viruses were phylogenetically related to members of the Bunyaviridae and Rhabdoviridae families, as well as the recently proposed Chuviridae. Our work expands our understanding of tick viromes and underscores the high viral diversity that is present in ticks. IMPORTANCE The incidence of tick-borne disease is increasing, driven by rapid geographical expansion of ticks and the discovery of new tick-associated pathogens. The examination of the tick microbiome is essential in order to understand the relationship between microbes and their tick hosts and to facilitate the identification of new tick-borne pathogens. Genomic analyses using unbiased high-throughput sequencing platforms have proven valuable for investigations of tick bacterial diversity, but the examination of tick viromes has historically not been well explored. By performing a comprehensive virome analysis of the three primary tick species associated with human disease in the United States, we gained substantial insight into tick virome diversity and can begin to assess a potential role of these viruses in the tick life cycle.